Pengaruh Media Pembelajaran Berbasis Aplikasi Canva Terhadap Minat Belajar Siswa Kelas V di Sekolah Dasar - Oktaviona Hajar; Suharmono Kasiyun; Rudi Umar Susanto; Akhwani Akhwani (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of using the Canva application on students' interest in learning Indonesian in class V at SDN Warugunung 1 Surabaya. The research method used is experimental research. Data collection by questionnaire method and documentation. The research instrument is a test sheet. The research sample was selected by purposive sampling, namely the VA class. The results showed that the average interest in learning not using Canva learning media was included in the low interest category, the average interest of students using Canva learning media was in the high category, and the comparison of the two resulted in quite significant differences, indicating that there was an effect of learning media using the Canva application on subjects. Indonesian towards increasing students' interest in learning at SDN Warugunung 1 Surabaya. Data processing is used to test the validity, reliability, normality test, homogeneity and hypothesis with the help of SPSS 24. Researchers believe that the developed learning media can be a solution in the development of interactive learning media that trains student creativity and student interest in learning.